The Influence of Influencer Marketing and Electronic Word of Mouth, on Purchase Intention Through Brand Image - Liapriyanti, Ade (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Advances in information and communication technology have had an impact on changes in the lifestyle of a person who makes social media a source of reference before deciding on a purchase. This study aims to determine and analyze the relationship between the influence of influencer marketing and electronic word of mouth on purchase intention through brand image on Facetology skincare products. The population of this study are consumers who know Facetology skincare through social media in the Jakarta area, with the criteria of following Facetology skincare social media accounts, knowing Facetology skincare products from influencer Tasya Farasya, aged at least 17 years, and domiciled in the Jakarta area. This type of research is quantitative with non-probability sampling method and the technique used is purposive sampling, 126 respondents collected questionnaires. The data analysis method uses SEM-PLS (Partial Least Square). The results showed that influencer marketing has a positive effect on brand image, influencer marketing has a positive effect on purchase intention, electronic word of mouth has a positive effect on brand image, brand image has a positive effect on purchase intention, electronic word of mouth variable did not have a positive effect on purchase intention. Influencer marketing has a positive effect on purchase intention through brand image and electronic word of mouth has a positive effect on purchase intention through brand image. In the future studies, researchers suggest expanding the research area and looking for object in other fields.